Learning module on the cultural identity of high school students from an educational institution in the district of San Juan Lurigancho, Lima - Arenales Solis, José C.E. (2024)
This article is the synthesis of the study to determine the influence of a learning module on the cultural identity of high school students from an educational institution (IE) in the district of San Juan de Lurigancho. It used a quasiexperimental design, censal sample of 40 students. Data was collected using the survey and a questionnaire. With the U tests of Mann-Whitney and Wilcoxon, it turned out that there is a significant difference between the scores of the experimental group compared to the control group. In this regard, it was concluded that the implementation of the module on district cultural heritage is effective in strengthening the local cultural identity of high school students; as it proved to strengthen the dimensions of the dependent variable (territorial identity, historical consciousness, cultural heritage), taking into account that in some cases the proposed themes were completely unknown.